A lithium alloy composite negative electrode material and its preparation method and application
By setting a conductive carbon material and a metal halide modification layer on the lithium alloy composite negative electrode material, the problems of lithium dendrites growth and side reactions are solved, the safety and cycle stability of lithium-ion batteries are improved, and the battery life is extended.
Patent Information
- Application Number
- CN202410688578.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-30
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-05-30
AI Technical Summary
The lithium metal negative electrode has problems with lithium dendrites in lithium-ion batteries, resulting in safety accidents and reduced energy efficiency, and high reactivity leads to instability of side reactions and electrolyte interface layer.
Using lithium alloy composite negative electrode material, by providing conductive carbon material and metal halide modification layer on the lithium alloy layer, lithium ion deposition and forming a stable solid electrolyte film are regulated, thereby reducing lithium dendrites' growth and side reactions.
It improves the safety and circulation stability of lithium metal batteries, reduces uneven deposition of lithium ions and electrolyte consumption, and extends the cycle life of the battery.
Smart Images

Figure CN118486809B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of negative electrode materials, and in particular relates to a lithium alloy composite negative electrode material and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries (LIBs) are widely used in portable electronic devices and electric vehicles due to their high energy density, long cycle life, and low self-discharge rate. However, the energy density of lithium-ion batteries is currently approaching its theoretical upper limit (300Wh kg -1 ), which limits the range of electric vehicles and leads to the so-called "range anxiety". Compared with commercial graphite anodes, lithium metal anodes are considered to be a strong candidate for further improving the energy density of lithium-ion batteries due to their ultra-high theoretical specific capacity (3860mAh / g) and extremely low electrochemical redox potential (-3.040V vs. standard hydrogen electrode). At the same time, lithium metal anodes can be widely matched with different types of positive electrode materials, such as conventional lithium-containing positive electrode materials or lithium-free positive electrode materials. However, in actual application, lithium metal anodes have the problem of lithium dendrite growth. The formed lithium dendrites may pierce the diaphragm, causing a short circuit between the positive and negative electrodes, thereby causing safety accidents such as battery thermal runaway.
[0003] The lithium metal batteries disclosed in the prior art have the following problems in the application process: First, the growth process of lithium dendrites is usually disordered and continuous, which increases the risk of lithium dendrites piercing the diaphragm of the liquid battery, and whether in the liquid battery or the solid-state battery, the growth of lithium dendrites may cause the battery cell to short-circuit. At the same time, lithium dendrites are a kind of "dead lithium", that is, they no longer participate in the charge and discharge reaction of the battery. Therefore, the generation of lithium dendrites means the continuous loss of active lithium, thereby reducing the available capacity and energy efficiency of the lithium metal battery. Secondly, due to its high reactivity, the lithium metal negative electrode is prone to side reactions with the electrolyte or solid electrolyte, and ultimately consumes the electrolyte while continuously generating a solid electrolyte interface layer (SEI film). In the subsequent cycle of the battery, the continuous formation and continuous rupture of the SEI layer cause the battery cell to fail; finally, due to the volume change of the lithium metal negative electrode during the battery charge and discharge process, lithium ions may be unevenly deposited on the negative electrode surface, thereby forming lithium dendrites, thereby increasing the risk of battery short circuit.
[0004] Therefore, in the art, there is an urgent need to develop a lithium metal negative electrode material with a stable structure, and the lithium metal battery assembled therefrom has good electrochemical performance and safety, so as to solve the above problems. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention aims to provide a lithium alloy composite negative electrode material and a preparation method and application thereof. The present invention improves the electrochemical performance and safety of lithium metal batteries by regulating the structure and composition of the lithium alloy composite negative electrode material.
[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a lithium alloy composite negative electrode material, the lithium alloy composite negative electrode material comprising a lithium alloy layer and a modified layer disposed on at least one side of the lithium alloy layer;
[0008] The material of the modification layer includes a conductive carbon material and a metal halide supported on the conductive carbon material.
[0009] Firstly, the present invention can regulate the uniform deposition of lithium ions on the surface of the lithium alloy composite negative electrode material, thereby forming a uniformly distributed interface deposition layer, thereby avoiding or reducing the growth of lithium dendrites or lithium powder, and improving the safety of lithium metal batteries; secondly, the surface of the lithium alloy composite negative electrode material provided by the present invention can form a solid electrolyte membrane (SEI) with a stable structure and not easy to break, thereby further improving the cycle stability of the lithium metal battery; finally, the modified layer arranged on the surface of the lithium alloy composite negative electrode material can isolate the lithium alloy layer from direct contact with the electrolyte, thereby reducing the occurrence of interface side reactions and reducing the consumption of liquid electrolyte.
[0010] Preferably, the conductive carbon material comprises a one-dimensional conductive carbon material.
[0011] Preferably, the one-dimensional conductive carbon material includes any one of single-walled carbon nanotubes, multi-walled carbon nanotubes or vapor-grown carbon fiber reinforcements, or a combination of at least two thereof, preferably vapor-grown carbon fiber reinforcements.
[0012] Preferably, the metal halide comprises any one of mercuric iodide, silver iodide or gallium iodide or a combination of at least two thereof, preferably mercuric iodide. The present invention preferably uses mercuric iodide to achieve better protection of metallic lithium and reduce the effect of its side reaction with the electrolyte.
[0013] Preferably, the mass ratio of the conductive carbon material to the metal halide is 1:(10-40), preferably 1:(20-30), for example, it can be 1:10, 1:12, 1:15, 1:18, 1:20, 1:22, 1:25, 1:28, 1:30, 1:32, 1:35, 1:38, 1:40, etc.
[0014] In the present invention, the deposition behavior of metallic lithium is better controlled by regulating the mass ratio of the conductive carbon material to the metal halide. Too low a mass ratio will cause a large amount of metallic lithium to be deposited on the surface of the modified layer, whereas a high mass ratio will reduce the lithium deposition kinetics.
[0015] Preferably, the lithium alloy layer comprises lithium alloy and lithium fluoride.
[0016] Preferably, the lithium alloy comprises any one of lithium molybdenum alloy, lithium chromium alloy or lithium tungsten alloy or a combination of at least two thereof, preferably lithium molybdenum alloy. The present invention preferably uses a combination of lithium molybdenum alloy and lithium fluoride, so as to achieve the technical effect that the mixed phase of lithium molybdenum alloy and lithium fluoride can effectively conduct lithium ions and reduce the barrier to lithium ion transmission.
[0017] Preferably, the mass ratio of the lithium alloy to lithium fluoride is (10-60):1, preferably (20-40):1, for example, it can be 10:1, 15:1, 20:1, 22:1, 25:1, 28:1, 30:1, 32:1, 35:1, 38:1, 40:1, 45:1, 50:1, 55:1, 60:1, etc.
[0018] In the present invention, the deposition behavior of metallic lithium is better controlled by regulating the mass ratio of lithium alloy and lithium fluoride. Too low a mass ratio will reduce the specific capacity of the negative electrode, whereas a high mass ratio will cause uneven deposition of metallic lithium.
[0019] Preferably, the thickness of the lithium alloy layer is 2 to 50 μm, preferably 10 to 20 μm, for example, 2 μm, 5 μm, 10 μm, 12 μm, 15 μm, 18 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, etc.
[0020] Preferably, the thickness of the modification layer is 1 to 5 μm, preferably 2 to 3 μm, for example, 1 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, etc.
[0021] In the present invention, the thickness of the modification layer is adjusted to better protect the metallic lithium. Too small a thickness will reduce the modification effect on the metallic lithium, and vice versa, the rate performance of the secondary battery will be reduced.
[0022] In a second aspect, the present invention provides a method for preparing the lithium alloy composite negative electrode material according to the first aspect, the method comprising the following steps:
[0023] The conductive carbon material and the metal vapor are mixed for the first time to obtain the conductive carbon material loaded with the metal vapor; the conductive carbon material loaded with the metal vapor and the halogen vapor are mixed for the second time to obtain the conductive carbon material loaded with the metal halide after the reaction, and the conductive carbon material is post-treated to obtain the modified layer;
[0024] The modified layer is compounded on at least one side of the lithium alloy layer to obtain the lithium alloy composite negative electrode material.
[0025] Preferably, the conductive carbon material needs to be pretreated before the conductive carbon material and the metal vapor are mixed for the first time.
[0026] Preferably, the pretreatment comprises subjecting the conductive carbon material to acid treatment and drying treatment in sequence.
[0027] Preferably, the acid-treated solution comprises dilute hydrochloric acid.
[0028] Preferably, the mass fraction of the dilute hydrochloric acid is 7.5-10%, for example, it can be 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, etc.
[0029] Preferably, the acid treatment time is 10 min.
[0030] Preferably, the temperature of the first mixing is 80-100° C., for example, 80° C., 85° C., 90° C., 95° C., 100° C., etc., and the time is 30 minutes.
[0031] Preferably, the temperature of the second mixing is 150-250°C, for example, 150°C, 180°C, 200°C, 220°C, 250°C, etc.; the time is 12-24h, for example, 12h, 14h, 16h, 18h, 20h, 22h, 24h, etc.
[0032] In the present invention, the first mixing and the second mixing are both carried out in a high pressure reactor. Preferably, the reaction is carried out under x-rays.
[0033] Preferably, the post-processing comprises a roller pressing process.
[0034] Preferably, the pressure of the roller pressing treatment is 3 MPa.
[0035] Preferably, the mass ratio of the conductive carbon material, the metal vapor and the halogen vapor is 1:1:(1-5), for example, it can be 1:1:1, 1:1:2, 1:1:3, 1:1:4, 1:1:5, etc.
[0036] Preferably, the method for preparing the lithium alloy layer comprises heating metal fluoride and molten lithium metal to obtain a composite material; and cooling the composite material to obtain the lithium alloy layer.
[0037] In the present invention, the preparation method of the metal fluoride exemplarily includes mixing 0.1 to 0.5 g of metal powder and hydrofluoric acid with a concentration of 0.05 to 0.5 mol / L, keeping it at a low temperature (minus 20° C. to minus 40° C.) for 10 min to 360 min, filtering and drying the solid for 8 hours to obtain the metal fluoride.
[0038] In the present invention, the molten lithium metal is lithium metal heated at 180°C.
[0039] Preferably, the heating is carried out in an inert atmosphere and a dry environment, for example, a vacuum glove box (H 2 O<0.1ppm,O 2 <0.1ppm).
[0040] Preferably, the heating temperature is 360-400°C, for example, 360°C, 370°C, 380°C, 390°C, 400°C, etc.
[0041] Preferably, the cooling is to room temperature.
[0042] In the present invention, the cooling time includes 1 to 15 minutes, for example, it can be 1 minute, 2 minutes, 5 minutes, 8 minutes, 10 minutes, 12 minutes, 15 minutes, etc.
[0043] In a third aspect, the present invention provides a negative electrode sheet, comprising a current collector and a negative electrode active material layer disposed on at least one side of the current collector, wherein the negative electrode active material layer comprises the lithium alloy composite negative electrode material according to the first aspect.
[0044] Preferably, the current collector comprises a copper-nickel current collector.
[0045] In a fourth aspect, the present invention provides a lithium metal battery, comprising a positive electrode sheet and a negative electrode sheet, wherein the negative electrode sheet comprises the negative electrode sheet according to the third aspect.
[0046] The negative electrode sheet provided by the present invention is not only applicable to liquid electrolyte systems, but also to semi-solid gel electrolyte systems and all-solid electrolyte systems. In addition, the negative electrode sheet provided by the present invention can match at least one of high-nickel positive electrode materials and lithium iron phosphate positive electrode materials.
[0047] Compared with the prior art, the present invention has the following beneficial effects:
[0048] The present invention provides a lithium alloy composite negative electrode material. Firstly, the present invention can regulate the uniform deposition of lithium ions on the surface of the lithium alloy composite negative electrode material, thereby forming a uniformly distributed interface deposition layer, thereby avoiding or reducing the growth of lithium dendrites or lithium powder, and improving the safety of lithium metal batteries; secondly, the surface of the lithium alloy composite negative electrode material provided by the present invention can form a solid electrolyte membrane (SEI) with a stable structure and not easy to break, thereby further improving the cycle stability of the lithium metal battery; finally, the modified layer arranged on the surface of the lithium alloy composite negative electrode material can isolate the lithium alloy layer from direct contact with the electrolyte, thereby reducing the occurrence of interface side reactions and reducing the consumption of liquid electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 This is a scanning electron microscope image of the lithium alloy composite negative electrode material provided in Example 1.
[0050] Figure 2 The cycle performance diagrams of the lithium metal batteries provided for Application Example 1 and Comparative Example 1 respectively. DETAILED DESCRIPTION
[0051] The technical solution of the present invention is further described below by combining the accompanying drawings and specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0052] Example 1
[0053] This embodiment provides a lithium alloy composite negative electrode material, such as Figure 1 As shown, the lithium alloy composite negative electrode material includes a lithium alloy layer and a modification layer arranged on one side of the lithium alloy layer; the material of the modification layer includes vapor-grown carbon fiber reinforcement (VGCF) and mercuric iodide loaded on the vapor-grown carbon fiber reinforcement.
[0054] Among them, the mass ratio of vapor-grown carbon fiber reinforcement and mercuric iodide is 1:22, and the thickness of the modified layer is 3μm; the lithium alloy layer includes lithium molybdenum alloy and lithium fluoride, the mass ratio of lithium molybdenum alloy and lithium fluoride is 25:1, and the thickness of the lithium alloy layer is 15μm.
[0055] This embodiment also provides a method for preparing the above-mentioned lithium alloy composite negative electrode material, and the preparation method comprises the following steps:
[0056] Preparation of lithium alloy layer:
[0057] 0.3 g of molybdenum metal powder was immersed in hydrofluoric acid with a concentration of 0.25 mol / L, and kept at -30°C for 150 min, after which the solid was filtered out and dried using a vacuum drying device for 8 h to obtain a metal fluoride powder;
[0058] The experiment was carried out in a dry glove box (H 2 O<0.1ppm,O 2 <0.1ppm), the dried metal fluoride powder and 10g of molten lithium metal (180°C) are fully and evenly mixed for 10min, and then 0.08g of nano silver particles are added as an auxiliary agent, followed by further full mixing for 30min, and the heating temperature is increased to 380°C to obtain a composite material; the composite material is coated on a copper-nickel composite current collector, and after cooling at room temperature for 7min, the coated membrane is rolled into a thin sheet using a pressure of 3 tons for standby use to obtain a lithium alloy layer.
[0059] Preparation of the modified layer:
[0060] The VGCF was immersed in 9% dilute hydrochloric acid, ultrasonicated in an ultrasonic machine for 10 minutes, and then dried in a 45°C blast oven for 1 hour for standby use; 10g of the dried VGCF was added to 10g of mercury metal, and the mixture was fully mixed in a 90°C high-pressure reactor for 30 minutes. At this time, the mercury metal was in a gaseous state and attached to the wall of the VGCF. The temperature was maintained continuously, and 30g of iodine was added after the reactor was depressurized. The iodine element needed to be placed separately, but in the same reactor. The reactor temperature was set to 200°C, and the reaction time was 18 hours. The high-pressure reactor was then transferred to an x-ray for reaction. Iodine vapor reacted with mercury to form mercuric iodide, which was attached to the VGCF. The VGCF was roller-pressed at a pressure of 3Mpa to obtain a modified layer with a thickness of 3μm.
[0061] Preparation of lithium alloy composite negative electrode materials:
[0062] A modification layer is stacked on one side of the lithium alloy layer, and a roll pressing process is performed under a pressure of 5 MPa to obtain the lithium alloy composite negative electrode material.
[0063] Example 2
[0064] The present embodiment provides a lithium alloy composite negative electrode material, which includes a lithium alloy layer and a modification layer arranged on one side of the lithium alloy layer; the material of the modification layer includes vapor-grown carbon fiber reinforcement (VGCF) and mercuric iodide loaded on the vapor-grown carbon fiber reinforcement.
[0065] Among them, the mass ratio of vapor-grown carbon fiber reinforcement and mercuric iodide is 1:22, and the thickness of the modified layer is 2μm; the lithium alloy layer includes lithium molybdenum alloy and lithium fluoride, the mass ratio of lithium molybdenum alloy and lithium fluoride is 38:1, and the thickness of the lithium alloy layer is 15μm.
[0066] This embodiment also provides a method for preparing the above-mentioned lithium alloy composite negative electrode material, and the preparation method comprises the following steps:
[0067] Preparation of lithium alloy layer:
[0068] 0.2 g of molybdenum metal powder was immersed in hydrofluoric acid with a concentration of 0.1 mol / L, and kept at -20°C for 10 min, after which the solid was filtered out and dried using a vacuum drying device for 8 h to obtain a metal fluoride powder;
[0069] The experiment was carried out in a dry glove box (H 2 O<0.1ppm,O 2 <0.1ppm), the dried metal fluoride powder and 10g of molten lithium metal (180°C) are fully and evenly mixed for 10min, and then 0.05g of nano silver particles are added as an auxiliary agent, followed by further full mixing for 30min, and the heating temperature is increased to 360°C to obtain a composite material; the composite material is coated on a copper-nickel composite current collector, and after cooling at room temperature for 2min, the coated membrane is rolled into a thin sheet using a pressure of 3 tons for standby use to obtain a lithium alloy layer.
[0070] Preparation of the modified layer:
[0071] The VGCF was immersed in 7.5% dilute hydrochloric acid, ultrasonicated in an ultrasonic machine for 10 minutes, and then dried in a 45°C blast oven for 1 hour for standby use; 10g of the dried VGCF was added to 10g of mercury metal, and the mixture was fully mixed in an 80°C high-pressure reactor for 30 minutes. At this time, the mercury metal was in a gaseous state and adhered to the wall of the VGCF. The temperature was maintained continuously, and 30g of iodine was added after the reactor was depressurized. The iodine element needed to be placed separately, but in the same reactor. The reactor temperature was set to 150°C, and the reaction time was 12 hours. The high-pressure reactor was then transferred to an x-ray for reaction. Iodine vapor reacted with mercury to form mercuric iodide, which adhered to the VGCF. The VGCF was roller-pressed at a pressure of 3Mpa to obtain a modified layer with a thickness of 2μm.
[0072] Preparation of lithium alloy composite negative electrode materials:
[0073] A modification layer is stacked on one side of the lithium alloy layer, and a roll pressing process is performed under a pressure of 2 MPa to obtain the lithium alloy composite negative electrode material.
[0074] Example 3
[0075] The present embodiment provides a lithium alloy composite negative electrode material, which includes a lithium alloy layer and a modification layer arranged on one side of the lithium alloy layer; the material of the modification layer includes vapor-grown carbon fiber reinforcement (VGCF) and mercuric iodide loaded on the vapor-grown carbon fiber reinforcement.
[0076] Among them, the mass ratio of vapor-grown carbon fiber reinforcement and mercuric iodide is 1:22, and the thickness of the modified layer is 5μm; the lithium alloy layer includes lithium molybdenum alloy and lithium fluoride, the mass ratio of lithium molybdenum alloy and lithium fluoride is 15:1, and the thickness of the lithium alloy layer is 15μm.
[0077] This embodiment also provides a method for preparing the above-mentioned lithium alloy composite negative electrode material, and the preparation method comprises the following steps:
[0078] Preparation of lithium alloy layer:
[0079] 0.5 g of molybdenum metal powder was immersed in hydrofluoric acid with a concentration of 0.5 mol / L, and kept at -40°C for 360 min, after which the solid was filtered out and dried using a vacuum drying device for 8 h to obtain a metal fluoride powder;
[0080] The experiment was carried out in a dry glove box (H 2 O<0.1ppm,O 2 <0.1ppm), the dried metal fluoride powder and 10g of molten lithium metal (180°C) are fully and evenly mixed for 10min, and then 0.1g of nano silver particles are added as an auxiliary agent, followed by further full mixing for 30min, and the heating temperature is increased to 400°C to obtain a composite material; the composite material is coated on a copper-nickel composite current collector, and after cooling at room temperature for 15min, the coated membrane is rolled into a thin sheet using a pressure of 3 tons for standby use to obtain a lithium alloy layer.
[0081] Preparation of the modified layer:
[0082] The VGCF was immersed in 10% dilute hydrochloric acid, ultrasonicated in an ultrasonic machine for 10 minutes, and then dried in a 45°C blast oven for 1 hour for standby use; 10g of the dried VGCF was added to 10g of mercury metal, and the mixture was fully mixed in a 100°C high-pressure reactor for 30 minutes. At this time, the mercury metal was in a gaseous state and adhered to the wall of the VGCF. The temperature was maintained continuously, and 30g of iodine was added after the reactor was depressurized. The iodine element needed to be placed separately, but in the same reactor. The reactor temperature was set to 250°C, and the reaction time was 24 hours. The high-pressure reactor was then transferred to an x-ray for reaction. Iodine vapor reacted with mercury to form mercuric iodide, which adhered to the VGCF. The VGCF was roller-pressed at a pressure of 3Mpa to obtain a modified layer with a thickness of 5μm.
[0083] Preparation of lithium alloy composite negative electrode materials:
[0084] A modification layer is stacked on one side of the lithium alloy layer, and a roll pressing process is performed under a pressure of 10 MPa to obtain the lithium alloy composite negative electrode material.
[0085] Example 4
[0086] The difference between this embodiment and embodiment 1 is that the mass ratio of the vapor-grown carbon fiber reinforcement to mercuric iodide is 1:5, and the rest is the same as embodiment 1.
[0087] Example 5
[0088] The difference between this embodiment and embodiment 1 is that the mass ratio of the vapor-grown carbon fiber reinforcement to mercuric iodide is 1:60, and the rest is the same as embodiment 1.
[0089] Example 6
[0090] The difference between this embodiment and embodiment 1 is that the mass ratio of lithium molybdenum alloy to lithium fluoride is 5:1, and the rest is the same as embodiment 1.
[0091] Example 7
[0092] The difference between this embodiment and embodiment 1 is that the mass ratio of lithium molybdenum alloy to lithium fluoride is 80:1, and the rest is the same as embodiment 1.
[0093] Example 8
[0094] The difference between this embodiment and embodiment 1 is that the vapor-grown carbon fiber reinforcement is replaced with an equal content of graphene, and the rest is the same as embodiment 1.
[0095] Example 9
[0096] The difference between this embodiment and embodiment 1 is that mercuric iodide is replaced by zinc iodide of the same content, and the rest is the same as embodiment 1.
[0097] Example 10
[0098] The difference between this embodiment and embodiment 1 is that the lithium-molybdenum alloy is replaced by a lithium-tin alloy with an equal content, and the rest is the same as embodiment 1.
[0099] Comparative Example 1
[0100] This comparative example provides a lithium metal negative electrode that has not been modified.
[0101] Comparative Example 2
[0102] The difference between this comparative example and Example 1 is that the material of the lithium alloy layer is replaced with a lithium metal layer with the same content, and the rest is the same as Example 1.
[0103] Comparative Example 3
[0104] The difference between this comparative example and Example 1 is that the material of the modification layer is replaced with lithium fluoride of the same content, and the rest is the same as Example 1.
[0105] Application Examples 1-10 and Comparative Application Examples 1-3
[0106] The lithium alloy composite negative electrode materials provided in Examples 1 to 10 and Comparative Examples 1 to 3 were assembled to obtain lithium metal batteries, and performance tests were performed. The test method is as follows:
[0107] The lithium alloy composite negative electrode materials provided in the examples and comparative examples were cut into discs with a diameter of 10 mm as negative electrode sheets; a polyethylene film with a thickness of 7 μm was used as the separator.
[0108] The positive electrode sheet is prepared by coating the positive electrode slurry of NCM811, polyvinylidene fluoride, Super P and carbon nanotubes with a mass ratio of 97.75:1:0.75:0.5 on the surface of the aluminum current collector and drying it. The surface density of the positive electrode sheet is 20 mg / cm 2 .
[0109] The electrolyte is prepared by mixing ethylene carbonate, dimethyl carbonate and lithium hexafluorophosphate in a mass ratio of 1:1:0.12.
[0110] The above-mentioned negative electrode sheet, positive electrode sheet, separator and electrolyte were assembled into a 10 mm button battery, and the cycle performance test was carried out at a rate of 0.5C / 1C until the retention rate reached 80%.
[0111] The test results are shown in Table 1:
[0112] Table 1
[0113]
[0114]
[0115] It can be seen from Table 1 that the lithium metal batteries provided in Application Examples 1-3 of the present invention have a long cycle life due to the use of lithium alloy composite negative electrode materials with a specific modified layer and further regulation of the composition of the lithium alloy layer.
[0116] By comparing Example 1 and Examples 4-5, it can be seen that the present invention better controls the deposition behavior of metallic lithium by controlling the mass ratio of the vapor-grown carbon fiber reinforcement and mercuric iodide.
[0117] By comparing Example 1 and Examples 6-7, it can be seen that the present invention adjusts the mass ratio of lithium-molybdenum alloy and lithium fluoride so that the lithium alloy composite negative electrode material has both high specific capacity and long cycle life.
[0118] By comparing Example 1 and Examples 8-10, it can be seen that other carbon materials, zinc iodide and lithium alloys disclosed in the prior art cannot achieve the technical effect of the lithium alloy composite negative electrode material in the present invention.
[0119] from Figure 2 It can be seen that the modified lithium alloy composite negative electrode material provided by the present invention still has a capacity retention rate of 98.75% after 100 cycles. However, the button battery assembled with the unmodified lithium metal negative electrode in Comparative Example 1 only has a capacity retention rate of 96.5% after 75 cycles.
[0120] Comparing Example 1 and Comparative Examples 2-3, it can be seen that replacing the lithium metal layer or the modification layer material used in the prior art cannot achieve all the technical effects of the present invention.
[0121] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A lithium alloy composite negative electrode material, characterized in that: The lithium alloy composite negative electrode material comprises a lithium alloy layer and a modified layer arranged on at least one side of the lithium alloy layer; The lithium alloy layer comprises lithium alloy and lithium fluoride, and the mass ratio of the lithium alloy to the lithium fluoride is (10-60):1; The lithium alloy includes any one of lithium molybdenum alloy, lithium chromium alloy or lithium tungsten alloy or a combination of at least two thereof; The material of the modified layer includes a conductive carbon material and a metal halide loaded on the conductive carbon material, and the mass ratio of the conductive carbon material to the metal halide is 1:(10-40); The conductive carbon material comprises a one-dimensional conductive carbon material; The metal halide includes any one of mercuric iodide, silver iodide or gallium iodide, or a combination of at least two of them.
2. The lithium alloy composite negative electrode material according to claim 1, characterized in that: The one-dimensional conductive carbon material includes any one of single-walled carbon nanotubes, multi-walled carbon nanotubes or vapor-grown carbon fiber reinforcements, or a combination of at least two of them.
3. The lithium alloy composite negative electrode material according to claim 2, characterized in that: The one-dimensional conductive carbon material is a vapor-grown carbon fiber reinforcement.
4. The lithium alloy composite negative electrode material according to claim 1, characterized in that: The metal halide is mercuric iodide.
5. The lithium alloy composite negative electrode material according to claim 1, characterized in that: The mass ratio of the conductive carbon material to the metal halide is 1:(20-30).
6. The lithium alloy composite negative electrode material according to claim 1, characterized in that: The lithium alloy is a lithium-molybdenum alloy.
7. The lithium alloy composite negative electrode material according to claim 1, characterized in that: The mass ratio of the lithium alloy to lithium fluoride is (20-40):
1.
8. The lithium alloy composite negative electrode material according to claim 1, characterized in that: The thickness of the lithium alloy layer is 2-50 μm.
9. The lithium alloy composite negative electrode material according to claim 8, characterized in that: The thickness of the lithium alloy layer is 10-20 μm.
10. The lithium alloy composite negative electrode material according to claim 1, characterized in that: The thickness of the modified layer is 1-5 μm.
11. The lithium alloy composite negative electrode material according to claim 10, characterized in that: The thickness of the modified layer is 2-3 μm.
12. A method for preparing a lithium alloy composite negative electrode material according to any one of claims 1 to 11, characterized in that: The method comprises the following steps: The conductive carbon material and the metal vapor are mixed for the first time to obtain the conductive carbon material loaded with the metal vapor; the conductive carbon material loaded with the metal vapor and the halogen vapor are mixed for the second time to obtain the conductive carbon material loaded with the metal halide after the reaction, and the conductive carbon material is post-treated to obtain the modified layer; The modified layer is compounded on at least one side of the lithium alloy layer to obtain the lithium alloy composite negative electrode material.
13. The method according to claim 12, characterized in that Before the conductive carbon material and the metal vapor are mixed for the first time, the conductive carbon material needs to be pretreated.
14. The method according to claim 13, characterized in that The pretreatment includes subjecting the conductive carbon material to acid treatment and drying treatment in sequence.
15. The method according to claim 14, characterized in that The acid-treated solution includes dilute hydrochloric acid.
16. The method according to claim 15, characterized in that The mass fraction of the dilute hydrochloric acid is 7.5-10%.
17. The method according to claim 14, characterized in that The acid treatment time is 10 min.
18. The method according to claim 12, characterized in that The temperature of the first mixing is 80-100° C. and the time is 30 minutes.
19. The method according to claim 12, characterized in that The temperature of the second mixing is 150-250° C. and the time is 12-24 hours.
20. The method according to claim 12, characterized in that The reaction was carried out under x-rays.
21. The method according to claim 12, characterized in that The post-processing includes a roller pressing process.
22. The method according to claim 21, characterized in that The pressure of the roller pressing process is 3 MPa.
23. The method according to claim 12, characterized in that The mass ratio of the conductive carbon material, the metal vapor and the halogen vapor is 1:1:(1-5).
24. The method according to claim 12, characterized in that The preparation method of the lithium alloy layer comprises heating metal fluoride and molten lithium metal to obtain a composite material; and cooling the composite material to obtain the lithium alloy layer.
25. The method according to claim 24, characterized in that The heating is performed in an inert atmosphere and a dry environment.
26. The method according to claim 24, characterized in that The heating temperature is 360-400°C.
27. The method according to claim 24, characterized in that The cooled to room temperature.
28. A negative electrode sheet, characterized in that: The negative electrode sheet comprises a current collector and a negative electrode active material layer disposed on at least one side of the current collector, and the negative electrode active material layer comprises the lithium alloy composite negative electrode material according to any one of claims 1 to 11.
29. The negative electrode sheet according to claim 28, characterized in that: The current collector includes a copper-nickel current collector.
30. A lithium metal battery, characterized in that: The lithium metal battery comprises a positive electrode sheet and a negative electrode sheet, and the negative electrode sheet comprises the negative electrode sheet according to claim 28 or 29.